An Econometric Study of the Relationship Between Consumer Spending and the Inflation Rate in Syria During the Period 1980-2021 (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aimed to determine the relationship between consumer spending and the inflation rate in Syria during the period 1980-2021, and to provide a comprehensive understanding of that relationship and its impact on the Syrian economy.The process of determining the appropriate model to model the relationship between consumer spending and the inflation rate through co-integration, and appropriate statistical models, such as the co-integration model, were used to analyze and interpret this relationship. Tests were conducted to ensure the quality of the model used in modeling the relationship between consumer spending and the inflation rate. This included analyzing random errors, such as standard error analysis, and estimating appropriate statistical indicators to evaluate the model’s performance.The results indicated that there is an inverse relationship between consumer spending and the inflation rate in Syria during the period 1980-2021, meaning that an increase in consumer spending leads to a decrease in the inflation rate, and vice versa.